THE PARTICIPATION OF THE UNIVERSITY PROFESSORS OF CORDOBA IN THE BUILDING OF THE NATION 1810-1853 - Vera de Flachs, María Cristina (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2011)
At the middle of the XIX Century, The National University of Cordoba, in Argentina, was a studies focus of small sized structure but it had a enormous prestige earned through its history. This institution there will be protagonist through its former students, and for the generation of the argentine Nation State. This paper will be devoted to the scrutiny of Cordoba University since the independence process, during this highly period, while the nation was struggling to reach its organization and get a Constitution. As well as, this paper shows moment when the university becomes ¨national¨.